PENGARUH BOPO DAN ROA TERHADAP CAR PADA PT BRI Tbk PERIODE 2007-2019 - Karyadi; R. Deden Adhianto (POLITEKNIK PIKSI GANESHA, 2020)
Abstract The purpose of this research was to determine the effect of Operational Cost of Operating Income (BOPO), and Return On Asset (ROA) on Capital Adequacy Ratio (CAR), at PT Bank Rakyat Indonesia Tbk for the 2007 to 2019 period. Sampling was based on purposive sampling, and tested with Classical Assumption Test, F Test, T Test, Regression Coefficient and Multiple Linear Regression. The research uses new data on the variables studied until 2019. Preliminary research generally uses a sample of the banking industry sector, while this research is specific to one company, namely PT Bank Rakyat Indonesia Tbk. The results of the study explain that simultaneously the BOPO variable and the ROA variable have a significant (negative) effect on the CAR variable based on the results of F count 21.165> 4.10 or F table / Sig 0.00 <0.05. While partially the BOPO variable affects significantly (negatively) based on the results of T count -5.559> 2.228 T table or Sig 0.00 <0.05), and the ROA variable affects significantly (negatively) the variable CAR with the result of T count -6.243 > 2,228 T table or Sig 0.00 <0.05. Keywords: BOPO, Return on Assets (ROA), Capital Adequacy Ratio (CAR).